2008
DOI: 10.1088/1751-8113/41/50/505002
|View full text |Cite
|
Sign up to set email alerts
|

The Yang–Lee edge singularity in spin models on connected and non-connected rings

Abstract: Renormalization group arguments based on a ıφ3 field theory lead us to expect a certain universal behavior for the density of partition function zeros in spin models with short-range interaction. Such universality has been tested analytically and numerically in different d = 1 and higher dimensional spin models. In d = 1, one finds usually the critical exponent σ = −1/2. Recently, we have shown in the d = 1 Blume–Emery–Griffiths (BEG) model on a periodic static lattice (one ring) that a new critical behavior w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…Three eigenvalues are equal by modulus exactly at the point where flipping occurs. Such a behaviour signals existence of a point with unusual Lee-Yang edge singularity exponent [56].…”
Section: Entropy Depletionmentioning
confidence: 99%
“…Three eigenvalues are equal by modulus exactly at the point where flipping occurs. Such a behaviour signals existence of a point with unusual Lee-Yang edge singularity exponent [56].…”
Section: Entropy Depletionmentioning
confidence: 99%
“…However, in the works [18,19,20] one has found another critical behavior (σ = −2/3). The models investigated in [18,19,20] have three-state per site and only nearest-neighbor interaction. Here we have shown that σ = −2/3 also appears in the one-dimensional spin-1/2 ANNNI model which contains a next-to-nearestneighbor interaction and only two states per site.…”
Section: Resultsmentioning
confidence: 99%
“…Even for one-dimensional spin models there are no analytic expressions for the Yang-Lee zeros in general. In order to save computer time, instead of using the analytic solution for Z N given in (4) in terms of the transfer matrix eigenvalues or in terms of the trace of powers of the transfer matrix as in Tr T N , we use an alternative 3 exact expression derived in [20] for any spin model which can be solved via a finite transfer matrix. Namely, since λ i , i = 1, 2, 3, 4 are solutions of the secular equation P 4 (λ) ≡ λ 4 − a 3 λ 3 + a 2 λ 2 − a 1 λ + a 0 = 0, we have shown, formula (11) of [20], that (4) can be identified with Z N = −N ln g 4 P 4 (1/g) g N = −N ln 1 − a 3 g + a 2 g 2 − a 1 g 3 + a 0 g 4…”
Section: Numerical Resultsmentioning
confidence: 99%
See 2 more Smart Citations